The permanence of temporary services: The reliance of Canadian federal departments on policy and management consultants. (18th September 2013) - Howlett, Michael; Migone, Andrea
Abstract: The use of external consultants in government management and policy realms has drawn increasing attention in many countries including Canada. Studies were undertaken internationally in the 1990s and 2000s as legislatures and their accounting arms became concerned with the hidden costs of "corporatization" of the public service and tried to expand benchmarking measures for government efficiency to include external consultants. Accounting for these increases in expenditures on consultancy, however, remains a challenge given the state of governmental financial and personnel reporting. The data on which existing reports have been drawn are very weak. This article examines results using a new dataset compiled from Proactive Disclosure reports in order to help clarify the situation of policy and management consulting in Canada at the departmental level.